Discrimination of dislocations in 4H-SiC by inclination angles of molten-alkali etched pits. (1st December 2022) - Yang, Guang; Luo, Hao; Li, Jiajun; Shao, Qinqin; Wang, Yazhe; Zhu, Ruzhong; Zhang, Xi; Song, Lihui; Zhang, Yiqiang; Xu, Lingbo; Cui, Can; Pi, Xiaodong; et al.
Abstract: Discrimination of dislocations is critical to the statistics of dislocation densities in 4H silicon carbide (4H-SiC), which are routinely used to evaluate the quality of 4H-SiC single crystals and homoepitaxial layers. In this work, we show that the inclination angles of the etch pits of molten-alkali etched 4H-SiC can be adopted to discriminate threading screw dislocations (TSDs), threading edge dislocations (TEDs) and basal plane dislocations (BPDs) in 4H-SiC. In n-type 4H-SiC, the inclination angles of the etch pits of TSDs, TEDs and BPDs in molten-alkali etched 4H-SiC are in the ranges of 27°−35°, 8°−15° and 2°−4°, respectively. In semi-insulating 4H-SiC, the inclination angles of the etch pits of TSDs and TEDs are in the ranges of 31°−34° and 21°−24°, respectively. The inclination angles of dislocation-related etch pits are independent of the etching duration, which facilitates the discrimination and statistic of dislocations in 4H-SiC. More significantly, the inclination angle of a threading mixed dislocations (TMDs) is found to consist of characteristic angles of both TEDs and TSDs. This enables to distinguish TMDs from TSDs in 4H-SiC.